The structural functionalisation of poly(ß-amino esters) for drug delivery to bacterial biofilms - Kasza, Karolina Anna (2024)
The prevalence of bacterial infections and the rise of antibiotic resistance pose an increasing challenge to human health, solutions to which are urgently needed. Of particular concern is bacterial assembly into biofilms associated with most bacterial infections, with biofilms demonstrated as more resistant to antimicrobial therapies than their planktonic counterparts. The decreased efficacy of conventional antibiotics when targeting biofilms is caused by several factors, including frequent poor penetration through the thick biofilm matrix and susceptibility to bacterial resistance mechanisms, leading to infection recurrence. Additionally conventional therapies are further hindered by their common poor aqueous solubility, off-target toxicity, and premature elimination, thus demonstrating a need for new, alternative treatments against bacterial infections. Drug delivery offers an attractive approach to tackling this challenge as it can improve the drugs pharmacokinetic and pharmacodynamic profiles, enable selective interactions with the infected tissue, and shield the antibiotic from resistance mechanisms, hence improving the therapeutics efficacy. The use of polymer-based drug delivery platforms is particularly of interest due to the versatile nature of polymeric materials, enabling the use of a range of biodegradable and non-biodegradable systems for the delivery of antimicrobials. Within the field of biodegradable polymers poly(ß-amino esters) (PBAEs) have recently attracted considerable attention, due to their facile synthesis and pH-responsive behaviour, leading to the wide application of these materials for gene delivery and in the assembly of polymeric micelles to transport cancer therapeutics. Comparatively the use of PBAEs to deliver antimicrobials has to date been limited and was therefore explored throughout this thesis. To evaluate the suitability of PBAEs for antimicrobial delivery we first addressed a significant limitation associated with their use to date, which involved the lack of a grafting-from methodology for the polymers post-synthetic functionalisation with additional copolymer chains. This was achieved by developing a novel approach to obtain ABA triblock copolymers, assembled by polymerising PBAEs with reversible addition chain transfer (RAFT) monomers, thus enabling the synthesis of polymer libraries with versatile functionalities. We then demonstrated successful particle assembly of the RAFT-PBAE-RAFT polymers, followed by subsequent encapsulation of a model hydrophobic drug within these systems, thus demonstrating their suitability for drug delivery. The RAFT-PBAE-RAFT particles were then evaluated in bacterial biofilm models, with the encapsulation and subsequent delivery of a quorum sensing inhibitor (QSI), administered in a combination therapy with the antibiotic ciprofloxacin (CIP). We demonstrated QSI encapsulation in RAFT-PBAE-RAFT particles can improve the efficacy of the antimicrobial, achieving an improved reduction in biofilm viability when administered as part of the combination therapy. We then set out to expand upon these results further, by attempting to further incorporated CIP in the RAFT-PBAE-RAFT drug delivery platform, through its conjugation to the RAFT copolymer. This approach was found to be unsuccessful, leading to a decrease in antibiotic efficacy following its permanent attachment to the polymer particles. To explore alternative methods for CIP delivery using PBAEs we then attached the antibiotic to linear PBAE chains and tested the efficacy of those systems in two different biofilm models, each time demonstrating an improvement of the antibiotic efficacy. Antibiotic attachment was further shown to delay the bacterial resistance response to the antimicrobial treatment, thus demonstrating this approach as an effective platform for CIP delivery. Overall, this thesis demonstrates the use of PBAE-based drug delivery systems is a versatile and attractive approach to enhance the efficacy of different antimicrobial compounds, particularly when targeting biofilm-associated infections.